Porphyromonas gulae and canine periodontal disease: Current understanding and future directions - Kyu Hwan Kwack; Eun-Young Jang; Cheul Kim; Young-Suk Choi; Jae-Hyung Lee; Ji-Hoi Moon (Virulence)
Porphyromonas gulae has emerged as a notable pathogen in canine periodontal disease, akin to Porphyromonas gingivalis in human periodontitis. This review examines the initial isolation, phylogenetic analysis, habitat, host range, relationships with host health status and age, and key pathogenic determinants, including fimbriae, proteases, citrullinating enzyme, and lipopolysaccharide. Control strategies discussed include polyphosphate to disrupt haeme/iron utilization, clindamycin with interferon alpha to reduce bacterial load and enhance the immune response, and a protease inhibitor. Further research is needed to understand strain-level diversity of virulence factors and interactions between P. gulae and other oral bacteria, particularly Fusobacterium nucleatum, a common pathogen in both dogs and humans. The potential for interspecies transmission between dogs and humans warrants further research into these interactions. Extensive in vivo studies across various breeds are crucial to validate the effectiveness of proposed treatment strategies. This review emphasizes P. gulae’s role in periodontal health and disease, setting the stage for future research and improved management of canine periodontal disease.